Health Information-Seeking Behavior of Iranian first-time Mothers and First-Time Pregnant Women in Northwest Health Centers of Tehran - sirous panahi; Farzaneh Mahmoudvand; Shahram Sedghi (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Pregnancy, especially the first pregnancy and childbirth, affects the women's quality of life. Improving information-seeking behavior facilitates the decision-making process of women during pregnancy and postpartum. The aim of this study was to investigate the health information-seeking behavior of Iranian first-time mothers and first-time pregnant women. Methods: This research was a cross-sectional-descriptive survey .A self-administered questionnaire was distributed among 358 first-time mothers and first-time pregnant women who attended 9 health centers in the northwest of Tehran, Iran, in 2017. Data were analyzed using SPSS version 24 and by conducting descriptive statistics and Kruskal-Wallis and Mann-Whitney U tests at .05 significance level. Result: The most important information need of the first- time mothers and first-time pregnant women was "Fetal/newborn health"; the most important source of information used was "gynecologist"; the most important way to access the resources was "visiting a doctor in person," and the most critical barrier to access information was "high costs of visiting a doctor, midwife, or nurse." Testing the hypotheses showed significant differences between information seeking components and demographic characteristics of the respondents. It was also found that there was no significant difference between the components of information-seeking behavior among two groups of first-time mothers and first-time pregnant women (p>0.05). Conclusion:  Making pregnancy-related health information more available and accessible and providing high-quality educational programs at affordable cost in health centers for first-time mothers and first-time pregnant women can help them increase their health literacy and prevent many common complications associated with pregnancy and child health.